Summary: Milestones in the evolution of south - Goin, Francisco Javier; Woodburne, Michael O.; Zimicz, Ana Natalia; Martin, Gabriel Mario; Chornogubsky Clerici, Laura
We summarize the configuration of plates, geographical barriers, and possible dispersal events during the Late Cretaceous–Cenozoic between North and South America, the Caribbean, Antarctica, and Australia. The arrival of metatherians in South America was a Late Cretaceous event, and probably a Maastrichtian one. There are few doubts that the first metatherians in this continent arrived from North America. We suggest that not only eutherian mammals but also metatherians may have reached South America from the north in a series of successive dispersal waifs. This FABI (First American Biotic Interchange) may have replicated the successive waif dispersal mood of the late Cenozoic GABI (Great American Biotic Interchange). The initial radiation of basal South American metatherian lineages (“Ameridelphia”) may have already occurred by Late Campanian-Maastrichtian times. We also suggest that a cooling pulse happening by the Latest Cretaceous (Late Maastrichtian, ca. 68–67 Ma) may have been involved in the origin of the Australidelphia, as part of the southern (Austral Kingdom) Nothofagus biota. Four out of six faunal phases were involved in the evolution of South American metatherians: (1) Early South American (Late Cretaceous to the Late Eocene), Late South American (Early Oligocene to late Miocene), Interamerican (Plio–Pleistocene), and Hypoamerican (Holocene). The first of these phases involved the arrival and expansion of many lineages and adaptive types. The global cooling by the Eocene–Oligocene Boundary implied the extinction of many (mostly tropical) lineages, as well as the diversification of several specialized ones. The third of these faunal phases transpired during a time lapse of ecological imbalance and global cooling, while the last phase saw already much impoverished metatherian associations throughout the continent. Fil: Goin, Francisco Javier. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones ...